Synthesis, crystallographic investigation, DFT studies and Hirshfeld surface analysis of novel bromo hydrazine derivative: (E)-2-(2-bromo-4, 5-dimethoxybenzilidene)-1-(4, 5-dimethoxy-2-methylphenyl)-1-hydroxyhydrazine. Issue 1 (1st June 2022) - Lalvani, Khushbu K.; Socha, Bhavesh N.; Patel, Urmila H.; Gandhi, Sahaj; Alalawy, Mohammed Dawood; Barot, V. M.; Patel, Mukesh
Abstract: A novel bromo hydrazine derivative: (E)-2-(2-bromo-4, 5-dimethoxybenzilidene)-1-(4, 5-dimethoxy-2-methylphenyl)-1-hydroxyhydrazine is synthesized and characterized by different relevant techniques. The Optical bonding conformed using 1 H NMR spectroscopic and Uv-vis studies. The crystallographic data confirmed that the bromo hydrazine derivative crystalizes in monoclinic space group P 21 / n and consists of bromo dimethoxy phenyl ring and methyl dimethoxy phenyl ring interlinked to each other via hydrazide moiety. The molecular geometry, HOMO-LUMO (frontier molecular orbital) energies, Molecular electrostatic potential (MEP), MPA (Mulliken population analysis), NBO (natural bond orbital), hypercharge polarizability of the title compound has been explored using Density Functional Theory (DFT) calculation via B3LYP method with LAV2P** basis set. Moreover, to visualize the intermolecular interactions and their distribution over the crystal structure, Hirshfeld surfaces and 3D energy framework analyses have been investigated using Crystal Explorer 17.5. In the absence of conventional forces, the weak but collective contribution of C-H…O/N/Br interactions along with direction specific π…π, C-H…π interaction having highest contribution from dispersion energy responsible for molecular stability. Lipophilicity index (log P value) represents significant biological activity of the molecule, correlates well with the contribution of C-H…π interaction. The probable binding modes between title molecule with different active sites of S. aureus (PDB code: 4ALI), E. coli (PDB code: 1QG6), colon cancer (PDB code: 2hq6), lung cancer (PDB code: 1x2j) and 1BNA (DNA) receptors are investigated by molecular docking studies using ArgusLab software.